2021- IFAD-UE/CCAFS CSA Monitoring: Fakara Climate-Smart Village (Niger) - Bonilla-Findji, Osana; Eitzinger, Anton; Ouedraogo, Mathieu; Läderach, Peter R.D.; Tougiani, Abasse (2021)
This dataset contains the files produced in the implementation of the “Integrated Monitoring Framework for Climate-Smart Agriculture” in the Fakara Climate Smart Village (Niger) in February 2021. This monitoring framework developed by CCAFS is meant to be deployed annually across the global network of Climate-Smart Villages to gather field-based evidence by tracking the progress on: adoption of CSA practices and technologies, as well as access to climate information services and their related impacts at household level and farm level